Pengaruh konsep diri, self efficacy dan motivasi terhadap Learning outcome mata pelajaran Aqidah Akhlak di kelas XI MA Pacet Mojokerto - Happy Ikmal (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2017)
Teaching and learning activities is a conscious activity and aims. Therefore, for these activities can be run well and achieve the expected goals, it must be done with the strategy or the right learning approach .. The purpose of this study were: 1) to describe the influence of Self-Concept on the results of studying chemistry at Class XI MA Pacet Mojokerto. 2) Describe the effect of self-efficacy on Learning outcomes chemistry in Class XI MA Pacet Mojokerto 3) Describe the effect of motivation on Learning outcomes chemistry in Class XI MA Pacet Mojokerto 4) Describe the relationship Self-concept, self-efficacy and motivation to Results studied chemistry at Class XI MA Pacet Mojokerto. From the results of the analysis can be summarized as follows: 1) There is a significant relationship between self-concept of the Learning outcomes chemistry inquiry model. T test against self-concept variables (X1) obtained regression coefficient (B) 0.440 (44.0%), coefficient (Beta) 0.091, tcount of 0.378 with significance 0.006 t. Because of the significance of t less than 5% (0.007 <0.05), the Nil Hypothesis (H0) is rejected and working hypothesis (Hi) is received. 2) There is a significant relationship between self-efficacy toward chemistry Learning outcomes inquiry model. T test for Self-efficacy variable (X2) obtained regression coefficient (B) 0.329 (32.9%), coefficient (Beta) 0.124, tcount of 0.436 with a significance of 0.009 t. Because of the significance of t less than 5% (0.008 <0.05), the Nil Hypothesis (H0) is rejected and working hypothesis (Hi) is received. 3) There is a significant relationship between motivation to learn chemistry results inquiry model. T test for motivation variable (X3) obtained regression coefficient (B) 0.130 (13.0%), coefficient (Beta) 0.065, tcount of 0.230 with a significance of 0.001 t. Because of the significance of t less than 5% (0.001 <0.05), the Nil Hypothesis (H0) is rejected and working hypothesis (Hi) received 4) From the calculation results obtained Fhitung value 2,249 (significance F = 0.001). So Fhitung> F table (2,249> 2:03) or Sig F <5% (0.001 <0.05). It means that together independent variables consisting of variable self-concept (X1), Self-efficacy (X2), motivation (X3) simultaneously to variable results of studying chemistry (Y).